The effect of Proteus mirabilis isolated from human urinary tract infections on the morphology of the rat kidney - Al-Ani, Imad Matloub Dally; Al-Murayati, H.Y.; Ghani, H.M. (2011)
Proteus mirabilis has previously been shown to be capable of persisting in the rat kidney for up to 8 weeks and induces many physiological changes following a single inoculation of the urinary bladder. The present study examined kidney tissue from infected animals for evidence of renal damage.The earliest histologic changes seen on the 2nd and 4th days, consisted of mild cellular sloughing and edema associated with mononuclear infiltration in the medulla and to a lesser extent in the cortex. On the 1st and following weeks, tubular atrophy, interstitial fibrosis, and a mononuclear infiltrate had advanced in the renal parenchyma re-sulting in chronic pyelonephritis. The observed renal degenerations with a corresponding ascending bacterial infection in the intra-renal reflux suggest that Proteus mirabilis is capable of producing chronic pyelonephritis in the rats after a single reflux challenge.